Factors associated with the use of oral health services in Peruvian children under the age of 12 years - José Diego Torres‐Mantilla; Edda E. Newball‐Noriega (Wiley, 2023)
Abstract Objectives To determine the prevalence and factors associated with the use of oral health services in Peruvian children under 12 years of age. Material and Methods A secondary analysis of 2019 Demographic and Family Health Survey was conducted. The sample consisted of 40,751 children. The main variable was the use of dental services (attended/not attended) in the last 6 months, and the independent variables were gender, age, area of residence, wealth quintile, health insurance coverage, information received on oral health care, age, and educational level of the caregivers. Analyses of absolute and relative frequencies, differences in proportions, and multivariate analysis using generalized linear models were performed. Results The dental service utilization prevalence during the last 6 months was 31%. Correlation was found with urban area residents (PRa = 0.945; 95% CI: 0.904-0.988), the Jungle geographical domain (PRa = 0.926; 95% CI: 0.877-0.977), the highest wealth quintile (PRa = 1.323; 95% CI: 1.232-1.421), the higher education level of the caregiver (PRa = 1.375; 95% CI: 1.231-1.536), affiliation with the Public Health Insurance (PRa = 1.112; 95% CI: 1.069-1.158), and the condition of having received information on oral health care (PRa = 2.355; 95% CI: 2.263-2.245) with respect to their baseline variables. Conclusions Several socio‐demographic factors were correlated with the use of oral health services in Peruvian children under 12 years of age and the percentage of their use was low. Information on oral health care had a more significant impact on both, the population from the highest wealth quintile and the highest educational attainment.